The Effect of Ear Acupuncture in Reducing Body Weight in Obesity Patients: A Meta-Analysis - Pangestu, Utami; Dewi, Yulia Lanti Retno; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Obesity is now no longer considered a health problem in developed countries, but has also been faced by developing countries such as Indonesia. According to WHO, obesity worldwide has increased by more than two times from 1980. In 2016, there were 1.9 billion adults who were overweight and more than 600 million of them were obese or overweight. This study aims to analyze the effect of ear acupuncture therapy on weight loss.Subjects and Method: This study was a systematic review and meta-analysis using the Randomized Controlled Trial design. The articles used in this study were obtained from several databases including PubMed, Google Scholar, Springerlink, Hindawi, and Sciencedirect. The articles used in this study were those published from 2008-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. P: obese patients (BMI ≥25), I: ear acupuncture therapy, C: no ear acupuncture therapy O: weight loss. The keywords for searching articles are as follows: